Driving monitoring system application with stretchable conductive inks: A review - Salim, Mohd Azli; Ab Wahid, Ameeruz Kama; Omar, Ghazali; Masripan, Nor Azmmi; Md. Saad, Adzni; Sudin, Mohd Nizam; Dobrota, Dan; Naroh, Azmi (Universiti Malaysia Perlis, 2020)
Nowadays the automotive industry is moving towards developing system connected vehicle parameters which can monitor the driver’s behaviour before driving. Most drivers lose focus and are emotionally distracted while driving owing to fatigue, drowsiness and alcohol consumption, that can result in a traffic accidents. The device or equipment used to detect the driver’s health before driving has always posed a problem in terms of the efficiency of the system especially concerning the cable connecting the equipment. Stretchable conductive ink (SCI) via electronic devices have been widely applied in various industries such as fabric, health, automotive, communications, etc. The flexibility allows a circuit to be placed on an uneven or constantly changing surface. However, till to-date, the effective use of the stretchable conductive ink has yet to be proven in the automotive industry. The current driver monitoring system cannot integrate with many of the driver's health level tracking features at one time. A combination of the driver’s monitoring system methods with stretchable conductive ink (SCI) sensors layout design can be used to prevent road accidents as a result of a driver’s behavior and will make the driving monitoring system more effective with soft substrates technology that has the advantage of geometric deformation based on appropriate shapes.